Pengaruh Bantuan Modal Terhadap Tingkat Pendapatan UMKM Di Kecamatan Baissappu Kabupaten Bantaeng - Syafika Nur Sabina; Ismail Rasulong; Wa Ode Rayyani (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study was to determine how much influence assistance has on the income level of MSMEs in Bissappu District, Bantaeng Regency. This type of research is descriptive quantitative, data processed with the needs of the model used. The data sources for this study were the results of interviews, documentation and data collection sheets (Questionnaires). The population in this study was 73 respondents. With data processing techniques, namely using classical assumption tests and hypothesis tests and analyzing data using SPSS 26 For Windows Software. The results of this study indicate that capital assistance (X) has a positive and significant effect of 0.000 <0.05 with a coefficient value of 0.827. So capital assistance positively and significantly affects the income level (Y) of micro, small and medium enterprises in Bissappu District, Bantaeng Regency.